The Meaningfulness of Sa Tidar Philosophy in Strengthening Community Civic Disposition - Sukron Mazid; Atsani Wulansari; Kokom Komalasari; Aim Abdulkarim; Rahmat Rahmat (Jurnal Moral Kemasyarakatan, 2025)
This research aims to discover the meaning of the philosophy of Sa Tidar as a symbol and meaning in the practice of life in Bukit Tidar, meaning that every wrong will be caught in every behavior in life. It means that honesty is part of one's integrity in action. Javanese thick norms impact social sanctions through community appreciation and rejection. The value of Sa Tidar is very relevant in the Civic Disposition value order as a reinforcement in community life. This research used a qualitative descriptive approach. The data were collected through observation, interview, and documentation. Then, the data was validated through source and method triangulation. This research used Miles and Huberman's model: data reduction, data presentation, and drawing conclusions to analyze the data. The results showed that the validity of Sa Tidar philosophy in strengthening Civic Disposition through (1) the meaning of Sa Tidar values has excellent relevance in shaping civic disposition as a pillar of social life. (2) The philosophy of Sa Tidar serves as a moral guide that integrates the values of religiosity and character in everyday life.